10TH JOINT CONFERENCE ON MATHEMATICS AND COMPUTER SCIENCE. ABSTRACTS - SOOS, Anna (2014)
The book contains the abstracts of 10th Joint Conference on Mathematics and Computer Science, hosted by the Faculty of Mathematics and Computer Science of the Babeș-Bolyai University, Cluj. The conference program, with four plenary talks and over 80 announced session talks, offered a great variety of excellent contributions in major areas of mathematics and computer science.